Absorption of Flavonoid Rutin after oral Treatment of Carica papaya Leaf Extract - WH Nugrahaningsih; Novi Latifa; Lisdiana Lisdiana (Biosaintifika: Journal of Biology & Biology Education, 2022)
Carica papaya leaves have many benefits, such as cancer treatment, lactation, digestive problem, and dengue fever. Papaya leaves contain various bioactive components such as alkaloids, flavonoids, tannins, saponins, carbohydrates, proteins, fats and steroids. Rutin is a flavonoid contained in Carica papaya leaf. Utilization of Carica papaya leaves as a herbal remedy requires data safety, effectiveness, bioavailability and stability of bioactive compounds of herbal medicine in the body. This study aimed to explore Carica papaya leaf extract's absorption by measuring the serial flavonoids in the plasma. The flavonoid profile of plasma was analogue by Rutin concentration profile. Time-series designs were conducted on fourteen rats were divided into seven groups. The single dose of papaya leaf extract (900 mg dissolved in 2 mL of aquadest) was given orally. Blood samples were collected about 1.5 mL at 0.5, 1, 2, 4, 6, 12 and 24 hours after oral administration. HPLC measured plasma Rutin flavonoid level. The maximum concentration (Cmax) was 0.026 mg/mL that reach 4 hours after oral administration (Tmax ). The half-time (t1/2) was 94.683 hours, and the area under the curve (AUC1-4) was 0.362 mg. h/mL. Carica papaya leaf extract was slowly absorbed and stayed in the plasma for a long time. The implication of the data of flavonoid profile can be used to manage the dose and frequency of extract oral treatment.